The next greatest engineering challenge - Abd Razak, Dzulkifli (2008)
THE magic of science and technology, especially in the various fields of engineering, have without a doubt provided great benefits to our lifestyles. Think about the many gadgets, that have made significant impact all round. Our lives were significantly changed, for instance, since 1900 when Nikola Tesla patented a "system of transmitting electrical energy" or when Eastman introduced his "Kodak Brownie camera". At the same time, among the greatest damage to Mother Earth are also the consequences of some of these engineering "feats". Not least are the addiction to fossil fuels and the carbon footprints left behind which have led to climate changes.